Processing math: 100%

First time here? Check out the FAQ!

Ask Your Question
1

How to solve this equation with double square root?

asked 7 years ago

ablmf gravatar image

I am trying to solve this equation in sage 4z2+24z2+11=0. But when I try the code

var('z')
eq = sqrt(-4*z^2 + 2*sqrt(-4*z^2 + 1) - 1) == 0
solve(eq,z)

I get

[z == -1/2*sqrt(2*sqrt(-4*z^2 + 1) - 1), z == 1/2*sqrt(2*sqrt(-4*z^2 + 1) - 1)]

Is there any way to actually solve it in sage?

Preview: (hide)

Comments

To better specify the question, do you want to solve for z in Z, Q, R, C, other?

slelievre gravatar imageslelievre ( 7 years ago )

One thing to notice is that expression=0 is equivalent to expression=0. This gets you rid of one of the square roots.

slelievre gravatar imageslelievre ( 7 years ago )

This has two solutions in C, ±233/2.

ablmf gravatar imageablmf ( 7 years ago )

If an answer solves your question, please accept it by clicking the "accept" button (the one with a check mark, below the upvote button, score, and downvote button, at the top left of the answer).

This will mark the question as solved in the list of questions on the main page of Ask Sage, as well as in lists of questions related to a particular query.

slelievre gravatar imageslelievre ( 7 years ago )

1 Answer

Sort by » oldest newest most voted
2

answered 7 years ago

slelievre gravatar image

updated 7 years ago

To better specify the question, one would need to say if we want to solve for z in Z, Q, R, C, or other.

Here we examine how to solve over C.

Define z as a symbolic variable, and define the equation (as you did).

sage: z = SR.var('z')
sage: eq_a = sqrt(-4*z^2 + 2*sqrt(-4*z^2 + 1) - 1) == 0

sage: solve(eq_a, z)
[z == -1/2*sqrt(2*sqrt(-4*z^2 + 1) - 1), z == 1/2*sqrt(2*sqrt(-4*z^2 + 1) - 1)]

First notice that expression=0 is equivalent to expression=0. This gets you rid of one of the square roots.

sage: eq_b = eq_a^2
sage: eq_b
-4*z^2 + 2*sqrt(-4*z^2 + 1) - 1 == 0

Then isolate the other square root.

sage: eq_c = eq_b + 4*z^2 + 1
sage: eq_c
2*sqrt(-4*z^2 + 1) == 4*z^2 + 1

Remove it by squaring. Note that the new equation is implied by the initial one, but no longer equivalent to it.

sage: eq_d = eq_c^2
sage: eq_d
-16*z^2 + 4 == (4*z^2 + 1)^2

Solve the new equation.

sage: sols_d = solve(eq_d, z)
sage: sols_d
[z == -1/2*sqrt(2*sqrt(3) - 3), z == 1/2*sqrt(2*sqrt(3) - 3), z == -1/2*sqrt(-2*sqrt(3) - 3), z == 1/2*sqrt(-2*sqrt(3) - 3)]

Check which of the solutions are solutions of the initial equation.

sage: [bool(eq_a.subs(s)) for s in sols_d]
[True, True, False, False]

Define the solutions of the original equation:

sage: sols_a = [s for s in sols_d if bool(eq_a.subs(s))]
sage: sols_a
[z == -1/2*sqrt(2*sqrt(3) - 3), z == 1/2*sqrt(2*sqrt(3) - 3)]
Preview: (hide)
link

Your Answer

Please start posting anonymously - your entry will be published after you log in or create a new account.

Add Answer

Question Tools

Stats

Asked: 7 years ago

Seen: 1,336 times

Last updated: Dec 31 '17